Endometrial Stem Cells and Reproduction. (12th January 2012) - Morelli, Sara S.; Yi, Pauline; Goldsmith, Laura T.
Abstract : Abnormal endometrial function remains a significant cause of implantation failure, recurrent pregnancy loss, and other pathologies responsible for female infertility. The development of novel therapies to treat infertility due to endometrial dysfunction requires an understanding of the latest advancements in endometrial cell biology, such as the role of endometrial stem cells. The remarkable regenerative capacity of the human endometrium is absolutely essential for successful reproduction and likely requires a population of stem cells in the endometrium. The purpose of this review is to provide an introduction to some of the newest concepts in endometrial stem cell biology.